Broadcasting In The Inevitability Of Digital Media Technology - Sari, Yunita; Nur Sya’adah, Siti; Nur Amaliah, Siti (International Journal of Educational Research & Social Sciences, 2024)
The main driver of this revolution was the discovery and development of digital technology. The discovery and development of digital technology. The essence of digi- tal technology is the process of converting all forms of information (text, sound, and graphics) encoded into a code containing the digits 0 and 1. This research is a qualitative research with a literature review approach. The data sources used are secondary data from various journals, books, news, videos and other texts relevant to this study. The results of the study found, digital technology opens up the possibility to produce higher quality media content, both in terms of "physical" quality and content, as well as quantity. quality media content, both in terms of "physical" quality and content, as well as quantity. But, digital information that is so easy to manipulate, edit and engineer, opens up the possibility to commit public lies, both in terms of plagiarism and in terms of falsifying information. On the one hand, increasingly affordable digital technology makes it possible for everyone to have greater access to information, both to receive and to disseminate information. On the other hand, there is the danger of dependence on technology, which in turn can make people bound (to certain hardware or software), and no longer free.